Environment, Ethics, and Entity Economics, Economia Aziendale. Historical and Ontological Aspects - Galassi, Giuseppe (De Computis, Revista Española de Historia de la Contabilidad., 2023)
The paper stresses the failure of ‘economics’ to predict and prevent repeated economic crises and the most critical topic of the environmental failure and ecological crises, founded also on economic theories and misconceived choices. The implication is a search for alternatives through an ontological-evolutionary-institutional approach and empirical investigations. The search for political ‘normative economics’, entity economics, accounting and information science copes with social and ecological-environmental problems, and systems science; it is necessary to keep always in mind these interactions for fully understand and correctly interpret the present ‘social-economic reality’. The problem concerning environmental decisions goes beyond ontology and belongs to ethics. It must underline the debates on ‘evolutionary ethics’, not only related with ‘environmental and ecological economics’, the management of environment and reporting, but also with ‘evolutionary ontology’; the new perspective affirms that ‘existence’, for instance, of a moral behavioral attitude, can reveal itself as a ‘norm’ thus relating ethics to ontology. General economists, entity economics theorists, as well as accountants and information scientists should be familiar with the potentials and limits of ‘ontology’, also for the ongoing expansion of computerization of scientific research in most of the scientific domains. The renewed interest, particularly in ontology, arouse specifically from systems scientists in constructing a wide variety of artificial intelligent systems. For its analysis, the study has been structured into two periods of time: until the middle of the 20th century and from that moment on. The paper ends by showing the new developments in information systems and their ontological approach.